Penerapan Kahoot dalam Peningkatan Kosakata Bahasa Mandarin Siswa Kelas X SMA Celebes Global School - Nurfadila Nurfadila; Misnawaty Usman; Abd. Kasim Achmad (Universitas Negeri Makassar, 2022)
ABSTRACT This research aims to improve students' Chinese vocabulary through the kahoot application. The sample of this research is 10 students of class X. This research is a classroom action research which consists of two cycles. Each cycle consists of two meetings. The instrument used is a test of increasing Chinese vocabulary and observation sheets. This study consisted of two, namely qualitative and quantitative. The results showed that the application of kahoot could increase students' Chinese vocabulary. This can be proven by the increase in students' Chinese vocabulary from the first cycle, the average obtained is 66.5 and in the second cycle with an average of 82. These results indicate that the students' Mandarin vocabulary has increased by 15.5.